Analisis Kebisingan dan Karakteristik Akustik Pengaruh AC Pada Kabin Penumpang Kereta Stainless Steel - Artianingrum, Imerlipta Sekar; Salim, Alfi Tranggono Agus; Rezika, Wida Yuliar; Hibbanurrohim, Muhammad Ibram; Nurdiansyah, Rahardian Titus (Universitas Muhammadiyah Yogyakarta, 2023)
A factor that affects the operation and comfort of passengers on trains is noise. The research problem is noise caused by air conditioning (AC) and acoustic characteristics in the passenger cabin of stainless steel trains against operational feasibility requirements. The purpose of the study was to analyze the noise and acoustic characteristics and noise distribution in the passenger cabin of the stainless steel train. The research method used is experimental quantitative which refers to ISO 3381: 2011 for noise measurement and ISO 3382: 2009 for acoustic characteristics. The result of the study is that the noise level in the passenger cabin of the stainless steel train increases linearly with the increase in measurement height and the reverberation time value shows different variations at each frequency. The conclusion of the research is that the stainless steel train passenger cabin meets the acceptance criteria of the Minister of Transportation Regulation Number: KM. 41 Year 2010 with noise results below 85 dBA and meets the criteria of a room that functions for conversation activities with a range of reverberation time values between 0.197 -0.357 second.